A Dual Therapeutic Approach to Diabetes Mellitus via Bioactive Phytochemicals Found in a Poly Herbal Extract by Restoration of Favorable Gut Flora and Related Short-Chain Fatty Acids - Singh A.K.; Kumar P.; Mishra S.K.; Rajput V.D.; Tiwari K.N.; Singh A.K.; Minkina T.; Pandey A.K.; Upadhyay P. (My University, 2025)
Diabetes mellitus (DM), a metabolic and endocrine condition, poses a serious threat to human health and longevity. The emerging role of gut microbiome associated with bioactive compounds has recently created a new hope for DM treatment. UHPLC-HRMS methods were used to identify these compounds in a poly herbal ethanolic extract (PHE). The effects of PHE on body weight (BW), fasting blood glucose (FBG) level, gut microbiota, fecal short-chain fatty acids (SCFAs) production, and the correlation between DM-related indices and gut microbes, in rats were investigated. Chebulic acid (0.368%), gallic acid (0.469%), andrographolide (1.304%), berberine (6.442%), and numerous polysaccharides were the most representative constituents in PHE. A more significant BW gain and a reduction in FBG level towards normal of PHE 600 mg/kg treated rats group were resulted at the end of 28th days of the study. Moreover, the composition of the gut microbiota corroborated the study’s hypothesis, as evidenced by an increased ratio of Bacteroidetes to Firmicutes and some beneficial microbial species, including Prevotella copri and Lactobacillus hamster. The relative abundance of Bifidobacterium pseudolongum, Ruminococcus bromii, and Blautia producta was found to decline in PHE treatment groups as compared to diabetic group. The abundance of beneficial bacteria in PHE 600 mg/kg treatment group was concurrently associated with increased SCFAs concentrations of acetate and propionate (7.26 nmol/g and 4.13 nmol/g). The findings of this study suggest a promising approach to prevent DM by demonstrating that these naturally occurring compounds decreased FBG levels by increasing SCFAs content and SCFAs producing gut microbiota. Graphical Abstract: Flow chart summarizing research on the dual therapeutic approach to diabetes mellitus via bioactive chemicals found in a poly herbal extract and the management of gut microbiota in relation to DM. (SCFAs, short chain fatty acids; SMB53, a genus of bacterial microbiota of small intestine; LPS, lipopolysaccharide) (Figure presented.) © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.